Gestión Presupuestaria de Ingresos del Gobierno Autónomo Descentralizado Municipal del Cantón Echeandía durante los periodos 2021 - 2022. - Toscano Escudero, Danny Rolando (2023)
The present case study is conducted in the Decentralized Autonomous Government of Canton Echeandía, the topic addressed is the budgetary management of revenues in the periods 2021 and 2022. The objective of the study is to analyze the management in terms of the use of the resources that the entity receives, for which a diagnosis was made, the sources of financing were identified and the percentage of compliance with the budget execution was evaluated. The methodology used is composed of a mixed approach study (qualitative-quantitative), the types of research used are: bibliographic and field, supported by deductive and inductive research methods; the scope of the study is descriptive, where the techniques applied are: documentary analysis and interview to the Financial Director of the institution. The results show that budget management is at an acceptable level; however, it has not reached levels of excellence, due to the fact that the percentage of deviation exceeds 20% in the two periods of analysis. The conclusions of the research are that the institution presents certain weaknesses in the management of the revenue budget, which requires timely adjustments to achieve better results that benefit the entity and in turn the citizens of the canton.